The networked principal. Issue 1 (2nd February 2015) - E. Price and Nienke M. Moolenaar, Heather; Moolenaar, Nienke M.; Sleegers, Peter J. C.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – While in everyday practice, school leaders are often involved in social relationships with a variety of stakeholders both within and outside their own schools, studies on school leaders' networks often focus either on networks within or outside schools. The purpose of this paper is to investigate the extent to which principals occupy similar positions in their school's network and the larger district network. In addition, the authors examined whether principals' centrality in both networks can be attributed to demographic characteristics and transformational leadership (TL). Design/methodology/approach – Using social network analysis, correlational and regression analysis, and an advanced social network technique, namely p2 modeling, the authors analyzed data collected among 708 educators in 46 Dutch elementary schools. The authors also offer a visualization of the district social network to explore principals' relationships with other principals in the district. Findings – Results suggest that principals who occupy a central position in their school's advice network are also more likely to occupy a central position in their district's collaborative leadership network. Moreover, TL was found to affect the extent to which principals are central in both networks. Originality/value – The study is unique as it simultaneously explores principals' social relationships in schools and the larger district. Moreover, the authors advance the knowledge of TL as a possible mechanism that may shape the pattern of these relationships, thereby connecting two streams of literature that were until now largely disconnected. Limitations to the study warrant further qualitative and longitudinal research on principals' social relationships in schools, districts, and the larger community.